The Influence Of Public Consumption Expenditure And Government Expenditure On Economic Growth In Indonesia - Aprinai, Tiara; Febrianti, Regita Putri; Adiwijaya, Adam Mulya; Noviarita, Heni (Lentera Ilmu Nusantara, 2024)
This article discusses the influence of public consumption expenditure and government expenditure on economic growth in Indonesia. In the context of macroeconomics, government expenditure consists of the purchase of goods and services, employee salaries, and transfer payments that function as a stimulus for the community. Public consumption spending, which includes primary needs such as food, clothing, and transportation, plays an important role in maintaining economic stability and creating jobs. The interaction between government spending and public consumption reinforces each other, where increased consumption drives production and income, which in turn improves people's welfare. Through this analysis, this article highlights the importance of the government's active role in managing expenditure to support sustainable economic growth in Indonesia.